Beispiel Nr: 68
$ \text{Gegeben:} y=ax^2+bx+c \\ \text{Gesucht:} \\ \text{Scheitel und Scheitelform}\\ \text{Definitions- und Wertebereich} \\ \text{Nullstellen - Schnittpunkt mit der x-Achse} \\ \text{Faktorisiere Form} \\ \text{Scheitel} \\ Eigenschaften\\ \textbf{Gegeben:} \\ y= 2x^2+3x-4\\ \\ \textbf{Rechnung:} \\\bullet \text{Funktion} \\ y= 2x^2+3x-4\\ \\ \bullet \text{Scheitelberechnung } \\ \begin{array}{l|l|l} \begin{array}{l} \text{quadratische Ergänzung } \\ \hline y=2x^2+3x-4 \\ y=2(x^2+1\frac{1}{2}x-2) \\ y=2(x^2+1\frac{1}{2}x+\left(\frac{3}{4}\right)^2-\left(\frac{3}{4}\right)^2-2) \\ y=2[(x+\frac{3}{4})^2-\left(\frac{3}{4}\right)^2-2] \\ y=2[(x+\frac{3}{4})^2-\frac{9}{16}-2] \\ y=2[(x+\frac{3}{4})^2-2\frac{9}{16}] \\ y=2(x+\frac{3}{4})^2-5\frac{1}{8} \\ Scheitel(-\frac{3}{4}/-5\frac{1}{8}) \end{array} & \begin{array}{l} \text{quadratische Ergänzung } \\ \hline y=2x^2+3x-4 \\ y=2(x^2+1\frac{1}{2}x)-4 \\ y=2(x^2+1\frac{1}{2}x+\left(\frac{3}{4}\right)^2-\left(\frac{3}{4}\right)^2)-4 \\ y=2[(x+\frac{3}{4})^2-\left(\frac{3}{4}\right)^2]-4 \\ y=2[(x+\frac{3}{4})^2-\frac{9}{16}]-4 \\ y=2(x+\frac{3}{4})^2-1\frac{1}{8}-4 \\ y=2(x+\frac{3}{4})^2-5\frac{1}{8} \\ Scheitel(-\frac{3}{4}/-5\frac{1}{8}) \end{array} & \begin{array}{l} \text{Scheitelformel} \\ \hline y=2x^2+3x-4 \\ xs=-\frac{3}{2\cdot 2} \\ xs=-\frac{3}{4} \\ ys=-4-\frac{3^2}{4\cdot2} \\ ys=-5\frac{1}{8} \\ Scheitel(-\frac{3}{4}/-5\frac{1}{8})\\ y=2(x+\frac{3}{4})^2-5\frac{1}{8} \end{array} \\ \end{array} \\ \\ \\\bullet\text{Definitions- und Wertebereich:}\qquad \mathbb{D} = \mathbb{R} \qquad \mathbb{W} = [(-5\frac{1}{8});\infty[ \\ \\=2(x+2,35)(x-0,851)\\ \\\bullet \text{Nullstellen / Schnittpunkt mit der x-Achse:} \\y= 2x^2+3x-4 = 0 \\ \begin{array}{l|l|l} \begin{array}{l} \text{a-b-c Formel}\\ \hline \\ 2x^{2}+3x-4 =0 \\ x_{1/2}=\displaystyle\frac{-3 \pm\sqrt{3^{2}-4\cdot 2 \cdot \left(-4\right)}}{2\cdot2} \\ x_{1/2}=\displaystyle \frac{-3 \pm\sqrt{41}}{4} \\ x_{1/2}=\displaystyle \frac{-3 \pm6,4}{4} \\ x_{1}=\displaystyle \frac{-3 +6,4}{4} \qquad x_{2}=\displaystyle \frac{-3 -6,4}{4} \\ x_{1}=0,851 \qquad x_{2}=-2,35 \end{array}& \begin{array}{l} \text{p-q Formel}\\ \hline \\ 2x^{2}+3x-4 =0 \qquad /:2 \\ x^{2}+1\frac{1}{2}x-2 =0 \\ x_{1/2}=\displaystyle -\frac{1\frac{1}{2}}{2}\pm\sqrt{\left(\frac{1\frac{1}{2}}{2}\right)^2- \left(-2\right)} \\ x_{1/2}=\displaystyle -\frac{3}{4}\pm\sqrt{2\frac{9}{16}} \\ x_{1/2}=\displaystyle -\frac{3}{4}\pm1,6 \\ x_{1}=0,851 \qquad x_{2}=-2,35 \end{array}\\ \end{array}\\ \underline{x_1=-2,35; \quad1\text{-fache Nullstelle}} \\\underline{x_2=0,851; \quad1\text{-fache Nullstelle}} \\ \\ \bullet \text{Vorzeichentabelle:} \\ \begin{array}{|c|c|c|c|c|c|c||} \hline & x < &-2,35&< x <&0,851&< x\\ \hline f(x)&+&0&-&0&+\\ \hline \end{array}\\ \\ \underline{\quad x \in ]-\infty;-2,35[\quad \cup \quad]0,851;\infty[\quad f(x)>0 \quad \text{oberhalb der x-Achse}}\\ \\ \underline{\quad x \in ]-2,35;0,851[\quad f(x)<0 \quad \text{unterhalb der x-Achse}}$